Efecto de mordientes sobre la variación de diámetro y tono de color en hilos de fibra de alpaca teñidos con flores de colli (Buddleja coriacea) - Lozano, Franklin (2024)
The aim of this study was to evaluate the effect of mordants on the variation of mean fibre diameter (MFD), spinning fineness (SF), and colour tone in alpaca fibre threads dyed with colli flowers (Buddleja coriacea). The dye was extracted using boiling water, followed by immersion of the thread in 160 ml of extract and post-mordanting with collpa, alum, and lemon salt at boiling temperature. MFD was measured using S-Fiber Med equipment. Colorimetry parameters were obtained using a spectrometer, and FT-IR spectrophotometer was used for identification of functional groups. MFD in colli-dyed and post-mordanted threads significantly increased with the addition of mordants, with the highest change observed with lemon salt (30.09 μm). The same trend was observed for SF. Dyeing with colli flower extract and subsequent mordant application produced different shades and hues of yellow colour in alpaca thread with significant variations in colorimetry parameters and FT-IR spectrum intensity. The reflectance spectrum R (%) showed a typical yellow colour curve with small differences in intensity due to the mordants used. In conclusion, MFD in colli-dyed thread increased by 0.44 µm; collpa mordanted by 2.78 µm; alum by 3.31 µm, and lemon salt by 3.51 µm compared to white thread, also producing different shades and hues of yellow colour with significant variations in colorimetry parameters and K/S. The sample dyed with colli without mordant presented the highest intensity, and lower intensity was observed in post-mordanted samples in FT-IR.